Masculine and Feminine Speech Styles of the Main Character in Mulan Live-Action (2020) and After the Ball (2015) Movies - Solichah, Hanif; Adila, Wildi (Universitas Negeri Medan, 2024)
This research aims to reveal the different types of masculine and feminine speech styles used in Wood’s (2008) theory and the functions of speech by Holmes (2013) in the main character of Mulan Live-Action (2020) and After the Ball (2015) Movies. This research used the qualitative method. The data were taken as textual data of the main character speech in both movies. The results were 173 data found belonging the types of masculine and feminine speech styles and the functions of speech in masculine and feminine speech styles. The types of masculine speech styles include establish status and control, instrumentality, conversational command, direct and assertive, abstract and, less emotionally responsive. Meanwhile, feminine speech styles include establish and maintain relationship, equality, support for others, maintenance work, responsiveness, personal and concrete style, and tentativeness. The research mostly found the types of masculine and feminine speech styles in this study. Personal and concrete styles of feminine speech were dominantly found because the two main characters, Mulan and Kate, often talk about personal experiences with others. The functions of speech include expressive, directive, referential metalinguistic, poetic, and phatic. In this study, the researcher mostly found speech functions except for poetic function. Referential functions were the dominant because the main character in both movies were frequently open to sharing information with others.